Un caso de hipertrofia bilateral de quelas en el cangrejo violinista Uca cumulanta (Decapoda: Ocypodidae) - Lira, Carlos (2006)
A case of bilateral cheliped hypertrophya crab Uca cumulanta (Decapoda: Ocypodidae). An adult male of Uca cumulanta with bilateral cheliped hypertrophy was found during a collection of crabs at La Restinga Lagoon, Margarita Island, Venezuela. Both chelipeds were sub equal in size, regarding the major cheliped of a normal male. Rev. Biol. Trop. 54 (Suppl. 3): 117-119. Epub 2007 Jan. 15